The Contribution of West Kalimantan Sufi Scholars In Promoting Community Resilience: The Great Works of The Sufis to Fulfill the Basic Needs of Societies - Elmansyah, Elmansyah; Nurhadijah, Elis; Gitosaroso, Muh.; Sahri, Sahri (Jurnal Theologia, 2024)
West Kalimantan is known as a region that produces Sufism thought, which is widely developed and utilized in various areas in Indonesia and the world. It can be seen from their great works in the form of books and development applications that they have created, even in integrating congregations. This research aims to reveal the works of West Kalimantan Sufism Ulama related to their efforts to build social, national and state resilience. The study is carried out over a long period, from 2012 to 2021. Several articles have been published in scientific journals and in book form. The research was conducted using a biographical approach through stories about their activities, the books they wrote, and other works still useful today. The study results show that Sufism scholars in West Kalimantan have their way of responding to changing times. The results of this work can be applied to Indonesia, which continues to grow towards becoming a developed and authoritative country.